2021
DOI: 10.3390/ijms22158332
|View full text |Cite
|
Sign up to set email alerts
|

Dual Nature of Relationship between Mycobacteria and Cancer

Abstract: Although the therapeutic effect of mycobacteria as antitumor agents has been known for decades, recent epidemiological and experimental studies have revealed that mycobacterium-related chronic inflammation may be a possible mechanism of cancer pathogenesis. Mycobacterium tuberculosis and non-tuberculous Mycobacterium avium complex infections have been implicated as potentially contributing to the etiology of lung cancer, whereas Mycobacterium ulcerans has been correlated with skin carcinogenesis. The risk of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 123 publications
(166 reference statements)
1
6
0
1
Order By: Relevance
“…In this meta-analysis, we reviewed their three treatment outcomes: the PFS and OS of LC patients with TB is longer than those without TB; the PFS and OS of LC patients with TB is shorter than those without TB; there was no statistically signi cant difference in OS and TTF between the two groups. This is consistent with the three main theories for the co-existence of lung cancer and TB: anti-cancer therapy can cause reactivation of TB; TB is a predisposing factor for lung cancer; or, it is random [30][31][32]. Some previous study has demonstrated that NSCLC patients with active TB show a better survival outcome; especially in squamous cell carcinoma [32][33][34].…”
Section: Discussionsupporting
confidence: 85%
“…In this meta-analysis, we reviewed their three treatment outcomes: the PFS and OS of LC patients with TB is longer than those without TB; the PFS and OS of LC patients with TB is shorter than those without TB; there was no statistically signi cant difference in OS and TTF between the two groups. This is consistent with the three main theories for the co-existence of lung cancer and TB: anti-cancer therapy can cause reactivation of TB; TB is a predisposing factor for lung cancer; or, it is random [30][31][32]. Some previous study has demonstrated that NSCLC patients with active TB show a better survival outcome; especially in squamous cell carcinoma [32][33][34].…”
Section: Discussionsupporting
confidence: 85%
“…NCFB represents a complex heterogeneous condition, and each underlining cause (COPD, infections, autoimmune diseases, genetic conditions, etc.) is known to impact differently on cancer risk [ 44 , 45 , 46 , 47 ]. To date, the chronic inflammatory process in COPD has been extensively analyzed, and different phenotypes associated with specific cytokine patterns favoring the tumor microenvironment have been identified [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zn 2+ is an essential but toxic microelement in high concentrations and can serve as an antimicrobial strategy for Mycobacterium [ 43 , 44 ], which can provoke chronic inflammation related to cancer pathogenesis [ 45 ]. Meanwhile, the P1B-type ATPase CtpG (Rv3270) was recently identified as a Zn 2+ efflux transporter via the CmtR-CtpG-Zn 2+ regulatory pathway that enhances mycobacterial resistance to Zn 2+ toxicity because the accumulation of Zn 2+ can contribute to ROS detoxification in mycobacterial cells [ 46 ].…”
Section: Metal Ions Participate In Innate and Adaptive Immune Activat...mentioning
confidence: 99%